Applications of microwave energy in gas production and tar removal during biomass gasification. Issue 12 (27th October 2020) - Guo, Feiqiang; Dong, Yichen; Tian, Beile; Du, Shilin; Liang, Shuang; Zhou, Nan; Wang, Yunpu; Chen, Paul; Ruan, Roger
Abstract : Microwave heating has the potential to promote gas production and tar removal during biomass pyrolysis or gasification based on its advantageous characteristics such as rapid heating and selective heating. Abstract : Biomass can be converted into renewable biofuels, employing thermochemical techniques, and thus has been considered as a promising alternative to fossil energy resources. Biomass gas which is generally produced via gasification can be used as a fuel for heat and power generation as well as raw gas for the production of liquid fuels or chemicals, and thus has been widely studied and commercially developed. Biomass gasification is a complex process mainly involving pyrolysis and subsequent gasification reactions, producing fuel gas and, inevitably, tar. Microwave heating has the potential to promote gas production during biomass pyrolysis or gasification based on its advantageous characteristics such as rapid heating and selective heating. Also, microwave irradiation can provide special heating conditions, produce unique phenomena, and form a microwave plasma torch, which may be an effective energy input to promote the cracking and reforming of biomass tar. Thus, the application of microwave energy in this field has attracted growing interest in the past few years. In this paper, a critical review is conducted on the recent progress of biomass gas production and tar cracking/reforming under microwave heating conditions, including chemical mechanisms, utilization of catalysts, and special phenomena triggered by microwave irradiation, which may provide useful information for optimizing biomass gasification technology for efficient fuel gas production. The present challenges and further development directions for these techniques are discussed as well.